The Functionalized UiO-66 Engineering for the Synergistic Enhancement of Mechanical Properties of Polydicyclopentadiene Nanocomposites - Gao, Feifei; Wu, Feiyang; Zhang, Xianyang; Jiang, Bowen; Li, Qizhong (Journal of inorganic and organometallic polymers and materials, 2023)
In this paper, zirconium-based MOF (Zr-MOFs) materials, namely UIO-66, UIO-66-NH 2 , GMA-UIO-66 and NB-UIO-66, were selected as fillers to enhance the mechanical properties of polydicyclopentadiene (PDCPD) nanocomposites, and Zr-MOFs/PDCPD nanocomposites were prepared by in situ polymerization. The functional groups and morphology of Zr-MOFs were characterized by Fourier transform infrared (FT-IR), X-ray diffraction (XRD) and field emission scanning electron microscopy (SEM). The mechanical properties of Zr-MOFs/PDCPD composites were studied by tensile toughness, notched impact strength and bending strength test. Furthermore, the optimum Zr-MOFs loading was determined. The results show that when the mass fraction of NB-UIO-66 is 0.4%, the composites’ tensile toughness, flexural strength, impact strength and heat distortion temperature (HDT) are simultaneously increased by 47.3%, 37.5%, 119.4%, and 59.2% respectively, compared with the pure PDCPD, which synergistically enhances the mechanical properties. Graphical Abstract